COVID-19, ; COVID-19, the oil price slump and food security in low-income countries - Maximilian Heigermoser; Thomas Glauben (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2020)
Covid-19 , - , , . (, ) - - . , , . , , . () . . , , , . . . – – The shutdown measures implemented to fight the Covid-19 pandemic resulted in a historic drop in crude oil prices, which implies existential challenges to countries depending on energy exports. The three largest crude oil exporters in Africa (Algeria, Angola and Nigeria) are - like numerous other raw material exporters worldwide - facing devaluing currencies and dwindling currency reserves. As food security in these states largely depends on imports of wheat and rice, domestic food prices are expected to rise due to the currency depreciation. This puts further pressure on populations with already low incomes, while local shutdowns and reduced economic activity lead to additional income losses. Recent panic buying and (temporary) export restrictions on international grain markets further exacerbate the situation. Not least due to currently ample grain stocks, such measures are not to be recommended. Instead, solidarity amongst nations, taking the form of emergency aid such as debt relief, food deliveries and medical aid, is required more urgently than ever. Furthermore, it is advisable to ease bureaucratic and tariff trade barriers to facilitate international trade. Demands for greater autarchy and de-globalisation should be avoided in the current precarious situation.
urn:nbn:de:gbv:3:2-123087
Keywords: 330; Shutdown; Ölpreis; Ernährungssicherung; Entwicklungsländer; Afrika